Evaluation of dual crop coefficient approach on evapotranspiration calculation of cherry trees - Guodong, Tong; Honglu, Liu; Fahu, Li (International Journal of Agricultural and Biological Engineering, 2016)
A simple way to estimate tree evapotranspiration is needed for orchard irrigation schedules and water management practice, and the dual crop coefficient (DCC) approach provides such a method. Plot experiments on cherry trees were conducted in an orchard of Beijing, China, from 2011 to 2013, to test the suitability and reliability of the DCC method. The calculated results from the DCC method were compared with those directly measured by water balance (WB) and sap flow (SF) methods. Results showed that total evapotranspiration in the whole growth period of cherry trees obtained by WB, SF and DCC methods was 560.0-569.3 mm, 544.7-569.8 mm and 564.1-574.6 mm, respectively. The Nash-Sutcliffe efficiency (NSE) and the ratio of root-mean-square error to the standard deviation of measured data (RSR) showed that the calculated total evapotranspiration by DCC method was consistent to that measured by the WB method at above “Satisfactory” level (0.50 < NSE  0.65 and 0.60 < RSR  0.70), and at “Very good” level (0.75 < NSE  1.00 and 0 < RSR  0.50) when compared to the SF method. However, the performance of the DCC method on monthly evapotranspiration was worse than on total evapotranspiration, and the consistency mostly was classified as “Unsatisfactory” (NSE  0.50 and RSR > 0.70) for the monthly evapotranspiration and as “Satisfactory” for the total evapotranspiration, respectively when compared with the WB and SF methods. Crop coefficients for the whole growth period were similar for all three methods, but the crop coefficient suggested by the DCC method was larger at the beginning and the late growth stages but smaller at the vigorous growth stage of cherry trees than those measured by using the WB and SF methods. It can be concluded that the DCC method is an effective tool to estimate total evapotranspiration in the whole growth period of cherry tree, but an improvement on accuracy of estimating monthly evapotranspiration of cherry trees is required. Keywords: dual crop coefficient method, crop coefficient, evapotranspiration, sap flow method, water balance method DOI: 10.3965/j.ijabe.20160903.1886 Citation: Tong G D, Liu H L, Li F H. Evaluation of dual crop coefficient approach on evapotranspiration calculation of cherry trees. Int J Agric & Biol Eng, 2016; 9(3): 29－39.